NOTARIS SEBAGAI PELAPOR DALAM PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG BERDASARKAN PERATURAN PEMERINTAH NOMOR 43 TAHUN 2015 - Adella Izzati Samiya; Heru Susetyo (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
In the eradication and prevention of money laundering, notaries should have taken part in informing such crimes. This is due to the notary being a Gate Keeper who can minimize the chance of obscuring the origin of the wealth that comes from a crime enjoyed by the perpetrator. Government Regulation number 43 of 2015 concerning Informing Parties in the Prevention and Eradication of Money Laundering Crimes emphasized that professionals such as notaries must inform if there are suspicious transactions involving their clients. Based on such regulation, the notary has a share where they must participate to minimize and prevent the occurrence of this money laundering crime.